Assessment of Knowledge, Attitude and Practices of Malaria among mothers of patients from 5 to 15 years of age in the District Bahawalnagar, Pakistan - Muhammad Rehan, Sana Saddique, Saleem Ahmad, Shumaila Nargus, Ruhamah Yousaf (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Malaria continues to be a serious global public health and development issue. Plasmodium falciparum, the most lethal type of the malaria parasite, is responsible for the great majority of malaria-related death and morbidity in children. Aim: To ascertain malaria knowledge, attitudes, and practices among mothers of patients aged 5 to 15 in the district of Bahawalgar, Pakistan. Methods: Study Design: Cross sectional Descriptive study. Settings: The study was done at District health quarter hospital Bahawalnagar. Duration of Study: The duration of study was 9 months from October to June. A questionnaire was used to collect the data from mothers of patients visiting medical OPD. Data was analyzed with SPSS version 25. Results: Findings of the study showed that a total of 241 malaria infected children were studied, to observe their plasmodium prevalence and their parental KAP of malaria. Most common age group of children was 13-15 years among 56.0%. Female’s children were commonest as 63.9%. Most of parents 46.1% were found with intermediate education. P-vivax was P-vivax was mostly seen among 66.4% children followed by p-falciparum 17.4%, p-malariae 3.3% and Plasmodium Vivax + falciparum 12.9%. The prevalence of plasmodiums was insignificantly related to demographic characteristics, with p-values that were relatively low. Conclusion: The study concluded that plasmodium vivax was the most prevalent malarial parasite. Parents had partial knowledge regarding malaria and its treatment. Parents had good attitude and agreed to participation in its prevention. Keywords: Malaria, parents, knowledge, practice, children’s mothers